Dampak Program Bantuan Tunai Langsung Dana Desa (BLT-DD) Terhadap Kesejahteraan Masyarakat Desa Polak Pisang Kecamatan Kelayang Kabupaten Indragiri Hulu Menurut Perspektif Ekonomi Syariah - Khairu Zade; Muhammad Apis Daulay; Taufik Hidayat (CV. ITTC INDONESIA, 2025)
This study aims to analyze the impact of the Village Fund Direct Cash Assistance (BLT-DD) program on the welfare of the people of Polak Pisang Village, Kelayang District, Indragiri Hulu Regency, according to a sharia economic perspective. The method used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation of 27 beneficiaries. The research findings show that BLT-DD has a limited impact on improving community welfare. Although this assistance helps to fulfill basic needs on a temporary basis, the effect is not significant enough to create sustainable economic change for the beneficiaries. In its implementation, the program still faces several obstacles, including delays in the distribution of assistance, the limited value of assistance, and the lack of community involvement in decision-making through village consultative meetings. From a sharia economic perspective, the implementation of BLT-DD has a positive impact on improving community welfare through the principles of social justice and concern for the poor. This assistance helps to fulfill basic needs and ease the economic burden, in line with the concept of i'anah and hibah in Islam. However, for the benefits to be sustainable, BLT-DD needs to be supported by sharia-based economic empowerment programs that encourage self-reliance and help.